The Effect of Organizational Culture on Organizational Citizenship Behavior with Job Satisfaction as Mediating Variable - Syaechurodji Syaechurodji; Karsikah Karsikah; Didit Haryadi (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
In an era characterized by rapid technological advancement and escalating organizational complexity, fostering a supportive organizational culture is paramount to enhancing employee attitudes and behaviors that contribute to institutional effectiveness. This study aims to investigate whether job satisfaction mediates the relationship between organizational culture and organizational citizenship behavior. A quantitative approach utilizing a causal research design was employed, leveraging Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze data collected from 150 university lecturers in Serang City, Indonesia, via a structured questionnaire with Likert-scale measurements. The empirical findings reveal that organizational culture exerts a significant positive effect on both job satisfaction and organizational citizenship behavior, while job satisfaction concurrently influences organizational citizenship behavior in a significant positive manner. Moreover, job satisfaction is confirmed to partially mediate the relationship between organizational culture and organizational citizenship behavior, thereby indicating that a constructive culture fosters discretionary employee behaviors by means of heightened satisfaction. In conclusion, reinforcing organizational culture is crucial for elevating job satisfaction and cultivating extra-role behaviors, which ultimately enhance overall organizational performance and sustainability within higher education institutions.